THE ANALYSIS OF FINANCIAL MANAGEMENT USING THE BOPO RATIO IN PAMSIMAS PROGRAM IN UJUNG KUBU VILLAGE, NIBUNG DISTRICT, BATUBARA REGENCY (TIME: JANUARY TO AUGUST 2021) - Zulia Rifda Daulay; Nirmalasari Nirmalasari; Cici Handayani; Sondang Sondang; Yuniar Astuti (Jurnal Ekonomi, 2023)
The Government of Indonesia implements the Community-Based Water Supply and Sanitation Program (Pamsimas-Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat), which is one of the national programs which is structurally organized by the Central Government to Local Governments to increasethe accessibilityof rural residents from scarcity of proper drinking water and proper of sanitation facilities by community based approach. The implementation of clean water service activities also needs to pay attention to management principles, because in running an organization it is very necessary to have management, especially in financial management.Financial Management of KPSPAMS Kubu Water of Ujung Kubu Village using a BOPO ratio (operational costs to operationalincome) is managed in a clean, responsible, transparency and professional system. This is a qualitative research or field research as the researchers explain this research in detail according to data and facts in the field and researchers also have curiosity in depth about the problems being studied in this study. The data used in this study is descriptive qualitative including an inductive approach for the research and emphasize on the subjectivity as well as the meaning of experience for individuals.The results of this study have a good impact on the people of Ujung Kubu Village because of the benefits of Pamsimas in analyzing financial management such as 1). In terms of health, 2) socio -cultural and 3) economic